Antibacterial activity of ceftizoxime (FK 749), a new cephalosporin, against cephalosporin-resistant bacteria, and its stability to beta-lactamase. - Kojo, H (1979)
Antibacterial activity of FK 749 against ampicillin-resistant clinical isolates of Escherichia coli was compared with those of other newly developed cephalosporins. FK 749 was the most active against strains possessing R-plasmids specifying ampicillin resistance and those whose resistance was chromosomally determined. The susceptibility of ampicillin-susceptible E. coli to FK 749 was not decreased by transduction of ampicillin resistance-specifying plasmids. However, most of the transconjugants acquired a high level of resistance to cefoperazone and cefamandole and a moderate level of resistance to cefoperazone and cefamandole and a moderate level to cefotiam. FK 749 was highly stable to both penicillinase- and cephalosporinase-type beta-lactamases, including R-plasmid-mediated beta-lactamase. Its level of resistance to beta-lactamases was comparable to those of cefoxitin, cefmetazole, and cefotaxime, slightly superior to that of cefuroxime, and much superior to those of cefotiam, cefamandole, and cefoperazone.